Heat-flow regimes and the hydrate stability zone of a transient, thermogenic, fault-controlled hydrate system (Woolsey Mound northern Gulf of Mexico). (January 2015) - Macelloni, L.; Lutken, C.B.; Garg, S.; Simonetti, A.; D'Emidio, M.; Wilson, R.M.; Sleeper, K.; Lapham, L.L.; Lewis, T.; Pizzi, M.; Knapp, J.H.; Knapp, C.C.; et al.
Abstract: This study aims to constrain the base of the hydrates stability field in structurally complexsites using the case of Woolsey Mound, a fault-controlled, transient, thermogenic hydrates system, in Mississippi Canyon Block 118, northern Gulf of Mexico. We have computed the base of the hydrates stability field integrating results from a recent heat-flow survey, designed to investigate geothermal anomalies along fault zones which exhibit different fluid flux regimes. An advanced "compositional" simulator was used to model hydrate formation and dissociation at Woolsey Mound and addresses the following hypotheses: 1. Migrating thermogenic fluids alter thermal conditions of the Hydrate Stability Zone (HSZ), so heat-flow reflects fault activity; 2. Gas hydrate formation and dissociation vary temporally at active faults, temporarily sealing conduits for migration of thermogenic fluids; 3. High salinity and inclusion of thermogenic gases with higher molecular weight than methane produce opposite effects on the depth to the bottom of the hydrate stability zone. Applications of results include identifying and quantifying hydrate deposits in shallow sediments using an interdisciplinary approach that includes multiple resolution seismic data evaluation, geological and geochemical groundtruthing and heat-flow analyses as a proxy for activity along faults. Highlights: Heat Flow study to characterize a fault-controlled hydrates system. The hydrates stability field presents multiple stability boundaries. Thermogenic fluids separate hydrates enriched in hydrocarbon heavier molecule.